Social Entrepreneurship in the Leadership of Grassroots Innovation Movement: A Case Study of Joglo Tani in Yogyakarta - Setiadi Setiadi (Humaniora, 2020)
This article is based on a case study in Joglo Tani, a local organization that focuses its programs on promoting new agricultural technology and urban farming while promoting food security for local people. It represents what characterizes the grassroots movement while destroying negative opinion about grassroots innovation. The success of Joglo Tani is influenced by the quality of leadership as social entrepreneurs as well as the quality of the network of activists and an organization that produce new, bottom-up solutions, and the ability of the solutions they produce to address local situations, concerning individual and social problems. The organizing of Joglo Tani innovations in the local realm has brought about a process of social transformation in rural areas, particularly in resource management and the system for organizing agricultural work. Through a voluntary movement, informal networks, and the ability to manage the potential of the environment, leadership is able to carry out the transformation process on an increasingly massive scale. This study proves that leadership in a bottom-up movement of ‘activist and organizational networks’ has succeeded in responding to the challenges of food supply limitations, moving towards sustainable food through instilling fundamental values of organizational life and technological breakthroughs as well as local institutions. Methodologically, the research was conducted through a comprehensive literature study stage related to grassroots innovation movements, while primary data collection was carried out through participatory observation, in-depth interviews, social and conventional media analysis, and interviews with community figures.